The Construction of Confidence Inter Vals for the Probability of Success for Hypergeometric Probability Distribution - (:unkn) unknown (My University, 2004)
Makalenin ana amacı hedef hipergeometrik dağılımı içeren başarı olasılıkları için, güven aralığı belirlemek amacıyla, bazı metotlar geliştirmektir. Bu amaç için bir kesin netice veren metot ile, binom, poisson ve normal ağılıma dayanan üç yaklaşık metot tariflenmiştir. Her metodu açıklayıcı örneklerde ilave edilmiştir. Makalemizde, çeşitli metotlar sunulduğu için her metodun kendine özel uygunluk şartları özellikle incelenmiştir. Güven aralığını yapılandırmada okuyucuya metot seçiminde yardımcı olmak için incelenen örneklerin neticeleri özetlenmiştir

The purpose of this article has been to describe some methods of constructing confidence intervals for the probability of success involving a hypergeometric distributionAn exact method and three approximate methods involving binomial, Poisson, and normal approximations have been described with examples illustrating the application of each procedure. The conditions for adequacy of each approximation have been designed. In order to assist the reader in assessing the options of the methods for the construction of confidence intervals, the results of the two examples considered in this paper are given so that the reader can easily make a comparison between the methods offered.